Nm Lipid Analysis of Platelet Membranes of Patients with Coronary Artery Diseases: Case Studies (Journal of Science and Technology, 2016)
A high - resolution proton nuclear magnetic resonance (Nmr) was used to investigate platelet membrane lipid composition of subjects who have been definitively diagnosed as having various forms of coronary heart disease (CAD). The one dimensional (1D) proton spectra were recorded at a temperature of 298° K in Fourier transform(FT) mode with 16K data points, using a 45° detection pulse and 2.0 acquisition time with a solvent presaturation during relaxation to remove excess water signal. The major phospholipids and cholesterol present were identified and estimated and compared to those of normal individual’s platelet membrane. Platelet cholesterol content as analysed by the proton Nmr in all the 3 patients investigated were significantly elevated (p